Skin barrier dysfunction as a risk factor for development of allergic disorders - Kowalewski, Cezary (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
The outermost layer of the skin, the stratum corneum, primarily mediates permeability barrier function. The formation of corneocytes is considered to be the result of a finely regulated differentiation process. During the terminal differentiation process structural change of the keratinocyte is associated with the sequential formation of differentiation marker proteins keratin 5 and 14 present in the stratum basale, keratin 1 and 10 in the stratum spinosum, and late differentiation marker proteins filaggrin, loricrin and involucrin in the granular layer. The granular layer is composed of secretory cells producing polar lipids and lipid converting enzymes. Polar lipids are packed into lamellar bodies and secreted into the intercellular space to be converted by enzymes to form non-polar lipid structures. The stratum corneum lipid matrix is constituted of ceramides, fatty acids and cholesterol. Small amounts of cholesterol esters and cholesterol sulfates are also present in the stratum corneum and both play a critical role in proper structural organization of the lipids, low pH, lipid crystallization, and the desquamation process, and therefore in normal barrier function. Currently, several skin diseases are known to show a genetic defect in epidermal permeability barrier function. The most representative include atopic dermatitis and ichthyosis vulgaris associated with atopic dermatitis. In atopic dermatitis abnormal lipid processing metabolism leads to deficiency of sphingosine – a natural antimicrobial agent – because of increased expression of sphingomyelin acylase. This results in colonization of the stratum corneum by Staphylococcus aureus and to ceramides deficiency induced by bacterial ceramidase activity, which eventually lead to barrier dysfunction. Repeated barrier disruption, whether environmentally or genetically determined, may stimulate signalling cascades that lead to inflammation and epidermal hyperplasia. Skin barrier dysfunction may also allow entry of allergens, which can lead to primary systemic sensitization. It has been shown that loss-of-function variations within the filaggrin gene are associated with dry skin phenotype and predispose to atopic dermatitis with allergic sensitizations, associated with increased asthma severity, and predispose to phenotypes involved in the atopic march.